Enhancing the role of domestic financial resources in Africa's development : a policy handbook (UN New YorkUS, 2009)
Highlights opportunities for increasing the types and levels of financial resources for Africa's development through an improvement in domestic financial resource mobilization and efficient use.
Keywords: FINANCIAL RESOURCES